Transcriptional interference and gene orientation in yeast: noncoding RNA connections. - Gullerova, M; Proudfoot, N (2010)
The compressed nature of genes in yeast requires that transcription units be well defined to prevent read-though transcription from one gene into an adjacent gene. Failure to terminate transcription may result in transcriptional interference of downstream-positioned genes. Transcriptional interference has been studied in several budding yeast gene systems and, interestingly, may be used as a general mechanism of gene regulation. The realization that extensive numbers of noncoding RNAs are transcribed between and across protein-coding genes greatly increases the complexity and subtlety of gene regulation through transcriptional interference. This may be achieved by somehow directly blocking RNA polymerase access to promoters or by the formation of repressive chromatin structures. Furthermore, in fission yeast, read-through transcription from convergent genes may generate double-strand RNAs. These will elicit RNA interference, resulting in heterochromatin formation and consequent gene silencing. Although much remains to be learned from yeast, it is apparent that higher eukaryotes also use related transcriptional interference and gene-silencing strategies. Even though protein-coding genes in mammals are widely separated along chromosomes, extensive numbers of noncoding RNAs are also synthesized. These may well connect distant genes and thus promote transcriptional interference and gene silencing, as is now well established for yeast.